Bailey & Scott's diagnostic microbiology - Tille, Patricia M. (St. Louis, Missouri : Elsevier, 2022)
Resource added for the {u200B}Laboratory Science Technician program 105065.
Resource added for the Microbiology 10-806-197 courses.
Basic medical microbiology -- General principles in clinical microbiology -- Approaches to diagnosis of infectious diseases -- Evaluation of antimicrobial activity -- Bacteriology -- Principles of identification -- Catalase-positve, gram-positive cocci -- Catalase-negative, gram-positive cocci -- Non-branching, catalase-positive, gram-positive bacilli -- Non-branching, catalase-negative, gram-positive bacilli -- Branching or partially acid-fast, gram-positive bacilli -- Gram-netative bacilli and coccobacilli (MacConkey-positive, oxidase-negative) -- Gram-negative bacilli and coccobacilli (MacConkey-positive, oxidase-positive) -- Gram-negative bacilli and coccobacilli (MacCoskey-negative, Oxidase-positive) -- Gram-negative bascilli and coccobacilli (MacCoskey-negative, Oxidase-variable) -- Gram-negative bacilli that are optimally recovered on special media -- Gram-negative cocci -- Anaerobic bacteriology -- Mycobacteria and other bacteria with unusual growth requirements -- Parasitology -- Mycology -- Virology -- Diagnosis by organ system -- Clinical laboratory management.
Previous edition: 2017.
Includes bibliographical references and index.
Keywords: Diagnostic microbiology -- Textbooks; Microbiological Techniques; Diagnostic Techniques and Procedures; Microbiological Phenomena; Diagnostic microbiology; Textbooks